The pedagogical management at the graduate level, from the perspective of students: practices and challenges in a public university - Navarro Rodríguez, Miguel (Avances en Supervisión Educativa, 2014)
In the present investigation, from an ethnographic perspective, is treated as the object of study the graduate teaching management of a public university, from the perspective of students. Are described in the results the analytical categories: management as a process, the practices and challenges for achieving better results, same as they are demanded by students finally various categories of contrast are set from the interviews with teachers. There is accord in both categorizations in certain practices of recognized quality, but not so in the challenges; because the students demand greater participation in the graduate colleges, where only teachers are participating. The students prioritize their demand of more quality in teaching, while teachers are evaluating their practices with more high levels in research, evaluation and academic organization.